Visions of Freedom - Gleijeses, Piero (University of North Carolina Press.)
During the final fifteen years of the Cold War, southern Africa underwent a period of upheaval with dramatic twists and turns in relations between the super powers. Americans, Cubans, Soviets, and Africans fought over the future of Angola, where tens of thousands of Cuban soldiers were stationed and over the decolonization of Namibia. Beyond lay the great prize: South Africa. This book provides an international history of this important theater of the late Cold War.
The Cuban drumbeat -- Neto, Castro, and Carter : a new beginning? -- The Cubans in Angola -- Strained relations : Cuba and Angola -- The fronts harden : the United States and Cuba, 1978-1980 -- Carter and Southern Africa : a balance sheet -- Enter Reagan -- The wonders of linkage -- Angolan travails -- The failure of Lusaka -- The United States, South Africa, and Savimbi -- The view from Cuba, 1984-1986 -- Havana and Moscow : conflicting strategies -- Negotiations in the offing? -- Cuito Cuanavale -- Maniobra XXXI aniversario -- Chester Crocker meets Jorge Risquet : talks about talks -- The negotiations -- The New York agreements -- Visions of freedom.
Includes bibliographical references (pages 613-639) and index.
JSTOR
Keywords: Africa, Southern -- History -- 1975-; Cold War -- Political aspects -- Africa, Southern; Africa, Southern -- Politics and government -- 1975-1994.; Africa, Southern -- Foreign relations -- 1975-1994.; Africa, Southern -- History -- Autonomy and independence movements; Afrique australe -- Histoire -- 1975-; Guerre froide -- Aspect politique -- Afrique australe; Afrique australe -- Politique et gouvernement -- 1975-1994.; Afrique australe -- Relations extérieures -- 1975-1994.; Afrique australe -- Histoire -- Autonomie et mouvements indépendantistes.; Autonomy and independence movements; Diplomatic relations; Politics and government; Southern Africa; Since 1975; History